The Relationship of Diet Knowledge and Type 2 Diabetes Mellitus Compliance with Long Prolanis Participation - Lydia Fanny; Thresia Dewi Kartini B; Fachriyani Fachriyani (Health Notions, 2021)
Knowledge of the diabetes mellitus diet is the first step in improving the adherence of DM patients to diet. The adherence of DM patients in running a diet is the main key to the stability of the health condition of DM patients. Knowing the relationship between nutritional knowledge and dietary compliance with type 2 DM with the length of participation of prolanis at the Blue Health Center, Bone Regency. Observational research with cross sectional approach. Measurement of nutritional knowledge using a questionnaire, measuring dietary compliance using a 24-hour recall form, and measuring the length of participation in prolanis using absenteeism during counseling. Data were analyzed by Chi Square test. Chi Square test, the p value is 0.595, meaning p>0.05, there is no relationship between nutritional knowledge and participation in prolanis. There is no relationship between nutritional knowledge of type 2 DM patients with length of participation in prolanis, but there is a relationship between type 2 DM dietary compliance with length of treatmen respondents are more active in doing prolanis activities, nutritional knowledge, and dietary compliance.Keywords: diabetes mellitus type 2; nutrition knowledge; diet compliance; prolanis